EDUCAÇÃO FÍSICA E GÊNERO: UMA ANÁLISE DOS JOGOS ESCOLARES DE MATO GROSSO DO SUL (2015 – 2019) - Wânia Costa da Silva (2023)
Our objective was to analyze the development process of the National and State Educational Policy, in Mato Grosso do Sul (MS), referring to School Physical Education and school games; as well as relating to gender relations and the identity construction of women in this context. We list, to meet that proposal, the following specific objectives: to highlight the path and the historical situation of School Physical Education in the National Educational Legislation, as well as the gender issues that pervade it and the insertion of women in Physical Education and Sports; to understand the State Educational Legislation - MS in the historical development in the field of School Physical Education with a focus on gender relations; to identify the propositions of school games, specifically the school games of Mato Grosso do Sul, with the promotion of students' participation in the event. The study was characterized by a qualitative approach, having as methodological procedures the bibliographical study and the documental analysis, which includes as sources the National Educational Legislation and that one of the State of Mato Grosso do Sul referring to School Physical Education and school sports, including the documents concerning the School Games of the state. As a result, we understand the historical process of insertion of School Physical Education in the Brazilian Educational legislation and the varied purposes that the area intended at different times, facing mishaps of a political, social and cultural nature. Society, through the role of the historically and culturally constructed female figure, impelled women to live below the male figure in terms of access to society's resources and forms of representation. In the sports field, historically considered a means of male supremacy, it took decades for women to be able to transit in it under the social judgment based on the bias of biological sex and the physical characteristics derived from it. In the mid-1930s, in Brazil, women with a sporting and adventurous spirit were pioneers in conquering spaces in the sports environment and, in later decades – such as the 1970s and 1980s – feminist movements began questioning and confronting the social character of the male and female. With regard to gender relations in the sporting sphere, with respect to the legislation analyzed and the documents of the School Games in Mato Grosso do Sul, it was found that gender relations linked to school sports practices are addressed in a generic way, there is no mention of the event being herald of gender parity and encourages girls to participate. Although sports spaces are no longer so clearly characterized as a field of disputes between genders, it is evident that parity of participation between genders, in the School Games of Mato Grosso do Sul, is not real; it is a reflection that social evolution is something unfinished, that the cultures, habits and ways of social relations of previous times are present in a surreptitious way in times that are called modern.